Praktik Manajemen Laba pada Sektor Consumer Non-Cyclicals di Indonesia: Peran Free Cash Flow, Financial Distress dan Kualitas Audit - Rachmaturrizqi; Mayangsari, Sekar (Ekonomi Digital, 2025)
This study aims to examine the effects of free cash flow, financial distress, and audit quality on earnings management. Employing a quantitative approach, the research utilizes secondary data from financial statements of consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method, resulting in 323 observations, which were analyzed using multiple linear regression techniques. The results reveal that both free cash flow and financial distress have a positive and significant effect on earnings management. Meanwhile, audit quality do not affect on earnings management. Among the control variables, firm size negatively affects earnings management, while leverage shows no significant effect. This research contributes to the existing literature by investigating the relationships between free cash flow, financial distress, and audit quality with earnings management, specifically within Indonesia's consumer non-cyclical sector. The study provides valuable insights into both financial and governance factors that drive earnings management practices among Indonesian corporations.